2023
DOI: 10.1101/2023.03.17.532897
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Overcoming donor variability and risks associated with fecal microbiota transplants through bacteriophage-mediated treatments

Abstract: Fecal microbiota transplantation (FMT) from a healthy donor to recurrent C. difficile infection (CDI) patients has proven efficient in curing the disease, possibly through bacteriophage-mediated (phages) modulation of the gut microbiome landscape. Fecal virome transplantation (FVT, sterile filtrated donor feces) has also been shown efficient for treating the disease. FVT has the advantage over FMT that no bacteria are transferred, but FVT does not exclude the risk of transferring eukaryotic viruses. We aimed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 161 publications
1
14
0
Order By: Relevance
“…Solvent/detergent treatment (approved by the World Health Organization for treating blood plasma 35 ) was used to inactivate enveloped viruses 36 (FVT-SDT), a compound (pyronin Y) that specifically binds to RNA 37,38 was applied to inactivate RNA viruses (FVT-PyT), and an optimized chemostat fermentation of intestinal inoculum aimed at removing the eukaryotic viruses by dilution 31 (FVT-ChP). We have also demonstrated that the modified FVT-SDT and FVT-ChP showed promising results in treating C. difficile infections in a mouse model 30 , which represents a simple disease etiology mainly caused by the toxin-producing C. difficile 39,40 . The more complex GM associated diet-induced obesity model 41 was included in this study to investigate whether the same modified FVTs 30 could be used to improve phenotypes from these two very different disease etiologies through phage-mediated restoration of a dysbiotic GM.…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…Solvent/detergent treatment (approved by the World Health Organization for treating blood plasma 35 ) was used to inactivate enveloped viruses 36 (FVT-SDT), a compound (pyronin Y) that specifically binds to RNA 37,38 was applied to inactivate RNA viruses (FVT-PyT), and an optimized chemostat fermentation of intestinal inoculum aimed at removing the eukaryotic viruses by dilution 31 (FVT-ChP). We have also demonstrated that the modified FVT-SDT and FVT-ChP showed promising results in treating C. difficile infections in a mouse model 30 , which represents a simple disease etiology mainly caused by the toxin-producing C. difficile 39,40 . The more complex GM associated diet-induced obesity model 41 was included in this study to investigate whether the same modified FVTs 30 could be used to improve phenotypes from these two very different disease etiologies through phage-mediated restoration of a dysbiotic GM.…”
Section: Introductionmentioning
confidence: 89%
“…We have also demonstrated that the modified FVT-SDT and FVT-ChP showed promising results in treating C. difficile infections in a mouse model 30 , which represents a simple disease etiology mainly caused by the toxin-producing C. difficile 39,40 . The more complex GM associated diet-induced obesity model 41 was included in this study to investigate whether the same modified FVTs 30 could be used to improve phenotypes from these two very different disease etiologies through phage-mediated restoration of a dysbiotic GM. Only male mice were included, since female mice are highly protected against diet-induced obesity 42 .…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations